Hubungan Antara Employee Engagement Dan Kepuasan Kerja Dengan Kinerja - Dhea Dana Mariska (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2018)
Performance is a result of employee behavior to perform tasks  according to competence. The Result of employee’s behavior in performing the duty is the employee’s attachment to the organization supported by the satisfaction while working. This researches was conduoted on employees of PT K. The number of reserch subjects is 100 people. All subjects work at least 1 year with minimal education DIII and age range 20–50 years. Hypotheses were tested by regression analysis.The result showed that there are a significant relationshop between employee engagement and job satisfacation and performance. (F = 30.622 ; R = 0.387). Employee engagement has a significant relationship with performance (r = 0.536; p = 0.00), and job satisfaction has significant relationship with performance (r= 0.448; p= 0.00). The results showed that there are an association of employee engagement and job satisfaction with performance.